Henoch-Schonlein purpura in mesothelioma - Joshi, S.; Pillai, S.; Chakera, Aron; Lee, Y. (2014)
© 2014 The Authors.Henoch-Schonlein purpura (HSP) is primarily a childhood immunoglobulin A (IgA)-mediated illness. When adults are affected, malignancy can be associated. We present a rare case of HSP in a 75-year-old man with malignant pleural mesothelioma. He presented with episodes of dizziness and subsequently developed non-palpable purpura across his legs, arthralgia, hematuria, proteinuria, and acute renal impairment. HSP was diagnosed based on clinical and histological findings on biopsy specimens from the skin and kidney that showed a leukocytoclastic vasculitis and mesangioproliferative glomerulonephritis with IgA deposits, respectively. He was treated with high-dose oral steroids with resolution of the skin and renal manifestations of the disease. HSP is rare in adults but has been linked to cancers. This is the first report of HSP in a patient with known malignant pleural mesothelioma.